Upaya Pencegahan Tindakan Perundungan Disabilitas di Kota Makassar - Yanlua, Siti Zainab; Yanlua, Nurfitri (Bacarita Law Journal, 2024)
Disabled people are minorities who are vulnerable to bullying because of their different characteristics. The impact of bullying is very detrimental because it can disturb their mental health, therefore preventive measures are needed so that they can be protected. Efforts to prevent acts of disability bullying that are carried out cannot only be carried out by one party, but require cooperation between persons with disabilities, families, schools, the community and the government. The government as the party that provides facilities then the community and families help prevent it by ensuring that no discrimination is experienced.